2009
DOI: 10.1037/a0015791
|View full text |Cite
|
Sign up to set email alerts
|

Transient auditory storage of acoustic details is associated with release of speech from informational masking in reverberant conditions.

Abstract: Perceptual integration of the sound directly emanating from the source with reflections needs both temporal storage and correlation computation of acoustic details. We examined whether the temporal storage is frequency dependent and associated with speech unmasking. In Experiment 1, a break in correlation (BIC) between interaurally correlated wideband or narrowband noises was detectable even when an interaural interval (IAI) was introduced. The longest IAI, which varied markedly across participants, could be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(68 citation statements)
references
References 54 publications
5
62
1
Order By: Relevance
“…However, the N1m and P2m latencies were both longer in older adults. These age-related increases are consistent with prior research (Matilainen et al, 2010;Tremblay et al, 2002) and may reflect a slowing in auditory processing and/or a broadening of the temporal integration window (Emmer et al, 2006;Gleich et al, 2007;Huang et al, 2009), with older adults reaching a saturation in the auditory evoked responses at a longer latency than young adults. An agerelated decline in temporal integration could also account for the reduced ORNm amplitude observed in our prior study (Alain and McDonald, 2007).…”
Section: Effects Of Age and Noise On The Speed Of Auditory Processingsupporting
confidence: 86%
“…However, the N1m and P2m latencies were both longer in older adults. These age-related increases are consistent with prior research (Matilainen et al, 2010;Tremblay et al, 2002) and may reflect a slowing in auditory processing and/or a broadening of the temporal integration window (Emmer et al, 2006;Gleich et al, 2007;Huang et al, 2009), with older adults reaching a saturation in the auditory evoked responses at a longer latency than young adults. An agerelated decline in temporal integration could also account for the reduced ORNm amplitude observed in our prior study (Alain and McDonald, 2007).…”
Section: Effects Of Age and Noise On The Speed Of Auditory Processingsupporting
confidence: 86%
“…The perceived co-location and perceived separation are based on perceptual integration of correlated sound waves delivered from each of the two loudspeakers. It has been confirmed that perceived target-masker spatial separation facilitates the listener's selective attention to target signals and significantly improves recognition of target signals (Freyman et al, 1999;Li et al, 2004;Wu et al, 2005;Rakerd et al, 2006;Huang et al, 2008Huang et al, , 2009. It should be emphasized that when the two loudspeakers are symmetrical to the listener, a change between the perceived co-location and the perceived separation alters neither the target-to-masker ratio in sound pressure level at each ear nor the stimulus-image compactness/diffusiveness (Li et al, 2004).…”
Section: Introductionmentioning
confidence: 82%
“…What is the role of the precedence effect in noisy, reverberant environments? In a (simulated) reverberant environment, to distinguish signals from various sources and particularly recognize the target source, listeners need to not only perceptually integrate the direct wave with the reflections of the target source (Huang et al, 2008(Huang et al, , 2009) but also to perceptually integrate the direct wave with the reflections of the masking source (Brungart et al, 2005;Rakerd et al, 2006). More specifically, when the delay between a leading sound (such as the direct wave from a sound source) and a correlated lagging sound (such as a reflection of the direct wave) is sufficiently short, attributes of the lagging sound are perceptually captured by the leading sound , causing a single fused sound image as coming from a location near the leading source (the precedence effect, see Wallach et al, 1949;Zurek, 1980;Freyman et al, 1991;Litovsky et al, 1999;Huang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Human listeners are highly sensitive to a temporal break in interaural correlation (BIC, a change of interaural correlation from 1 to 0, then back to 1) (Akeroyd and Summerfield, 1999;Boehnke et al, 2002;Huang et al, 2009a;Huang et al, 2009b;Li et al, 2009). When a BIC occurs at the temporal middle of binaurally presented identical noises, introducing such a drop in interaural correlation does not alter the energy and spectrum but modifies the perceptual compactness/diffuseness, number, placement, and/or loudness of the noise object (Blauert and Lindermann, 1986;Hall et al, 2005).…”
Section: Introductionmentioning
confidence: 98%